2002
DOI: 10.1182/blood-2002-07-2297
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 therapy dramatically alters peripheral T-cell homeostasis in normal and SIV-infected nonhuman primates

Abstract: Interleukin-7 (IL-7) is important for thymopoiesis in mice and humans because IL-7 receptor ␣ (IL-7R␣) mutations result in a severe combined immunodeficiency phenotype with severe thymic hypoplasia. Recent evidence has indicated that IL-7 also plays an important role as a regulator of T-cell homeostasis. Here we report the immunologic effects of recombinant human IL-7 (rhIL-7) therapy in normal and simian immunodeficiency virus (SIV)-infected nonhuman primates. Cynomolgus monkeys receiving 10 days of rhIL-7 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
193
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 38 publications
12
193
4
1
Order By: Relevance
“…In SIV-infected macaques, IL-7 induced the proliferation of naive T cell subsets within the CD4 ϩ and CD8 ϩ T cell populations that acquire a "memory-like" phenotype as previously described both in mice and macaques (28,59) (data not shown), impairing our ability to properly quantitate T cell subsets following IL-7 treatment. In contrast, IL-15 mainly increased the Ki-67 marker on CD4 ϩ and CD8 ϩ effector memory T cells (Fig.…”
Section: Il-15 Significantly Increases Ki-67 Expression On Both Effecmentioning
confidence: 76%
See 3 more Smart Citations
“…In SIV-infected macaques, IL-7 induced the proliferation of naive T cell subsets within the CD4 ϩ and CD8 ϩ T cell populations that acquire a "memory-like" phenotype as previously described both in mice and macaques (28,59) (data not shown), impairing our ability to properly quantitate T cell subsets following IL-7 treatment. In contrast, IL-15 mainly increased the Ki-67 marker on CD4 ϩ and CD8 ϩ effector memory T cells (Fig.…”
Section: Il-15 Significantly Increases Ki-67 Expression On Both Effecmentioning
confidence: 76%
“…Both IL-7 and IL-15 are cytokines produced by stromal cells that directly affect the homeostatic proliferation of memory T cells and regulate effector function (63,64). Prior studies on naive or SIV-infected macaques treated with rIL-7 protein have demonstrated that this cytokine alters T cell homeostasis (27,28,65) without altering SIV replication (66). The use of rIL-15 has been pioneered in naive macaques alone or together with Ags (26) and has been demonstrated to increase the frequency of long-lived CD4 ϩ and CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous administration of IL-15 or induction of host expression of IL-15 in wildtype mice by reagents, such as poly I:C, lipopolysaccharide (LPS) and type I-IFNs, causes a selective increase in the proliferation of CD8 + CD44 high T cells in vivo [29][30][31]. Exogenous administration of IL-7 to mice enhances T-cell number and function [32,33] and, in both intact and immunodeficient non-human primates, causes a considerable yet reversible increase in the circulating levels of naïve and Ag-experienced CD4 + and CD8 + T cells [34]. Although similar studies have yet to be conducted in humans, there is evidence to support an inverse correlation between serum levels of IL-7 and the severity of lymphopenia caused by conditions, such as AIDS and cytotoxic drug therapy (reviewed in Ref.…”
Section: Evidence For the Presence Of Homeostatic Cellular Cytokine 'mentioning
confidence: 99%